MACC: Inovasi Media Pembelajaran Accurate Online Berbasis Android - Sulastri Sulastri; Andryani Andryani (Jurnal Pendidikan Ekonomi (JUPE), 2023)
One of the accounting software introduced in schools is Accurate Online. However, the Accurate Online learning media used in schools still needs to be further developed to be able to support teaching and learning activities more optimally. Therefore, the researcher wants to develop an Android-based Accurate Online learning media. The research phase carried out by the researcher refers to the ADDIE model. Several teachers and students at the Institute for Accounting and Finance Vocational High School who introduced Accurate Online, a media expert, a material expert, and 30 students (limited users) were the subjects of this study. The research data were collected by interview and questionnaire techniques. Researchers used descriptive qualitative techniques and descriptive quantitative percentages for data analysis. The result of this research is the Android-based Accurate Online learning media which has been declared very feasible by experts and limited user